Assessing the Immune Cell Subset and Genetic Mutations in Patients With Palindromic Rheumatism Seronegative for Rheumatoid Factor and Anti–Cyclic Citrullinated Peptide. Issue 2 (5th January 2023) - Yang, Chin‐An; Li, Ju‐Pi; Lai, Yi‐Hua; Huang, Ya‐Ling; Lin, Chien‐Yu; Lan, Joung‐Liang
Abstract : Objective: The etiology underlying cases of palindromic rheumatism (PR) not associated with other rheumatic diseases in patients who are seronegative for rheumatoid factor and anti–cyclic citrullinated peptide (seronegative PR) is unclear. We aimed to investigate the immune cells and genes involved. Methods: This was a single‐center comparative study of 48 patients with seronegative PR and 48 healthy controls. Mass cytometry and RNA sequencing were used to identify distinct immune cell subsets in blood. Among the 48 seronegative PR patients, plasma samples from 40 patients were evaluated by enzyme‐linked immunosorbent assay for cytokine levels, and peripheral blood samples from 25 patients were evaluated by flow cytometry for mononuclear cell subsets. Plasma samples from 21 patients were evaluated by real‐time polymerase chain reaction for differential gene and protein expression, and samples from 3 patients were analyzed with whole‐exome sequencing for gene mutations. Results: Immunophenotyping revealed a markedly increased frequency of CD14+CD11b+CD36+ and CD4+CD25–CD69+ cells in seronegative PR patients with active flares compared with healthy controls ( P  < 0.0001 for both cell subset comparisons). Gene enrichment analyses of RNA‐sequencing data from sorted CD14+CD11b+CD36+ and CD4+CD25–CD69+ cells showed involvement of the inflammatory/stress response, phagocytosis, and regulation of apoptosis functional pathways. Up‐regulated expression of CXCL16 and IL10RA was observed in monocytes from PR patients. Up‐regulation of PFKFB3, DDIT4, and TGFB1, and down‐regulation of PDIA6 were found in monocytes and lymphocytes from PR patients with active flares and PR patients in intercritical periods. Plasma levels of S100A8/A9 and interleukin‐1β were elevated in PR patients. Whole‐exome sequencing revealed novel polygenic mutations in HACL1, KDM5A, RASAL1, HAVCR2, PRDM9, MBOAT4, and JRKL . Conclusion: In seronegative PR patients, we identified a distinct CD14+CD11b+CD36+ cell subset that can induce an inflammatory response under stress and exert antiinflammatory effects after phagocytosis of apoptotic cells, and a CD4+CD25–CD69+ T cell subset with pro‐ and antiinflammatory properties. Individuals with genetic mutations involving epigenetic modification, potentiation and resolution of stress‐induced inflammation/apoptosis, and a dysregulated endoplasmic reticulum stress response could be predisposed to seronegative PR.